Sistem Informasi Pendaftaran Surat Izin Masuk Kawasan Konservasi (SIMAKSI) Pada Jalur Pendakian Gunung Kerinci Dan Danau Gunung Tujuh Berbasis Web - Firnando, Muhammad Ridho; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2022)
Currently outdoor mountain climbing activities are very popular in Indonesia, marked by the increasing number of visitors, both local tourists and foreign tourists every year, When you want to climb, prospective climbers must have (SIMAKSI) a permit to enter the conservation area from the TNKS area manager (Taman Nasional Kerinci Seblat). Thus the management of the Gunung Kerinci hiking trail and Danau gunung Tujuh is often overwhelmed by the surge in visitors on major holidays such as school holidays, Republic of Indonesia Independence Day and the end of the year, because the charging process is still conventional SIMAKSI manual. The goal that the researcher wants to achieve is to be able to design an information system for registration of permits to enter conservation areas (SIMAKSI) so that the manager can improve the quality of service providers. Data collection was carried out by interviewing TNKS. other than that, The system development method used is a prototype with UML (Unified Modeling Language) and Adobe XD tools to design the user interface. The output of this research is an online SIMAKSI registration